Pelatihan dan Pendampingan Pengembangan Kapasitas Usaha Klasterisasi Pengolahan Buah Nanas Menjadi Sari Buah dan Selai Nanas - Imam Habibi; Titik Irawati; Nunuk Helilusiatiningsih; Edy Soenyoto (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2021)
Pineapple was a potential commodity in Kediri Regency, favored because of its sweet taste mixed with acid which contains nutrients and antioxidants. The community service activity involves Faculty of Agriculture UNISKA in collaboration with the Pineapple Farmer Group and PT. PNM Kediri Branch. The purpose of the activity was identifying problems with pineapple farmers through survey activities, solving problems through training activities. Pineapple processing in Kediri district was not yet fully implemented. Still maintaining sales in fresh form so it was necessary to add value to the product. The training was held in September 2019. The tools and materials used were a set of cooking utensils and pineapple fruit. The expected output of activities was in the form of a cluster map of pineapple plant farmers in Kediri district and product diversification from pineapple plants. The results obtained were that farmers can produce fruit juice, pineapple jam and pineapple business assistance.